075 Gamma-glutamyltransferase as a predictor for alcohol- and non-alcohol-related cancer incidence. (16th November 2010) - Strohmaier, S; Borena, W; Strasak, A; Goebel, G; Edlinger, M; Diem, G; Concin, H; Kelleher, C; Ulmer, H
Abstract : Objective: Recent evidence suggests that elevated levels of gamma-glutamyltransferase (GGT) are associated with both incidence and mortality of cardiovascular disease and cancer. Although GGT is regarded as a marker of liver function which may in turn reflect alcohol consumption, to date, no study has investigated the relationship of GGT with cancer sites known to be alcohol-related or non-related. Design: Prospective cohort follow up and linkage study. Participants and setting: First visit measurements in 94 628 adult women and 80 224 men screened for metabolic risk factors as part of a standardised primary care assessment in Vorarlberg province of Austria. During a median follow-up of 13 years, a total of 5136 incident cancers were diagnosed in men and 4665 in women. Methods: Sex-specific Cox proportional hazards models, adjusted for age, body mass index and smoking were performed to estimate HRs and 95% CI per quintiles of GGT. Results: In males, the highest GGT-quintile revealed a high risk of alcohol-related cancer incidence (HR 2.20, 95% CI 1.74 to to 2.78). The association was strongest for cancers of the liver and intrahepatic bile ducts (HR 16.50, 4.00–68.19), followed by cancers of the lip, oral cavity, pharynx and larynx (HR 3.80, 2.33–6.20), esophageal cancer (HR 2.39, 1.01–5.72) and colorectal cancer (HR 1.36, 1.01–1.83). In females, there was a modest but significant association between GGT and alcohol-related cancers (HR 1.16, 1.02–1.32). GGT showed a significant association in breast cancer only (HR 1.19, 1.02–1.39). HRs were clearly elevated for cancers of the liver and intrahepatic bile ducts and for cancers of the lip, oral cavity, pharynx, larynx and oesophagus, however, without reaching significance due to limited number of cases. No association was seen for colorectal cancer. Additionally, elevated GGT was found to be significantly related to cancers with weak or no evidence of alcohol consumption as a risk factor. In males, there were associations with pancreatic cancer (HR 2.13, 1.01–4.56), lung cancer (HR 2.04, 1.55–2.70), bladder cancer (HR 1.76, 1.11–2.77) and kidney cancer (HR 1.61, 0.92–2.82, p for trend=0.009). In females, the association was most pronounced in cervical cancer (HR 3.77, 1.94–7.32), followed by lung cancer (HR 1.63, 1.02–2.60) and endometrial cancer (HR 1.42, 0.98–2.05, p for trend=0.013). Conclusion: Although elevated GGT levels were strongly associated with incidence of alcohol-related cancers, most markedly in men, there were still effects of GGT in non-alcohol related cancer sites. This suggests that alcohol consumption explains the relationship between GGT and cancer outcomes only in part.